Carbon dioxide management for product supply chain and total site utilisation and storage - Mohd Nawi, Wan Norlinda Roshana (2018)
The development of insight-based graphical and algebraic techniques in process integration (PI) for carbon dioxide (CO2) emission targeting, design, and planning based on pinch analysis (PA) has evolved in line with the developments of other PI tools for the conservation of resources including heat, mass, gas, power, and electricity. Complementary PA-based tools can provide graphical and visualisation insights that are vital for better conceptual understanding of problems, particularly at the onset of CO2 emission systems planning and design, have been developed over the last ten years. Therefore, a comprehensive and systematic CO2 emissionreduction planning and management using PA-based methods are proposed in this research to provide a systematic and vital insights towards CO2 emission reduction. This research proposes a methodology for CO2 emission reduction throughout product supply chain and end-of-pipe management of CO2 via total site integration. A palm cooking oil product is used to demonstrate the proposed methodology development. In the first step, CO2 emission hotspot which contributes the highest emission phase in the supply chain is identified. Next, the most suitable and economically viable CO2 reduction strategies are identified and screened by using CO2 management hierarchy as a guide, and SHARPS as a cost screening technique. At this stage, a total of 1,077 tonnes per year (t/y) CO2 emissions for a basis of 100 t/y of palm cooking oil production are successfully reduced to 402 t/y which is approximately 63% reduction based on the implementation of CO2 emission reduction strategies that achieved target payback period (TPP ≤ 2 years) and investment cost (INV ≤ USD 150,000). In the third step, the remaining CO2 emission could be further reduced with end-of-pipe emission management considering multiple sites which can act as CO2 sources or demands. A methodology for total site CO2 integration is introduced to integrate and fully utilise the CO2 emissions among industries and/or plants via single and multiple centralised header before being sent to storage to permanently store and zero CO2 emissions can be achieved via single header. Finally, CO2 purification and pressure drop are considered during CO2 transportation in the total site CO2 integration system’s design. An algebraic approach called CO2 utilisation and storage-problem table algorithm is proposed to obtain total site target for integration of CO2 utilisation and storage. In conclusion, a new integrated methodology of CO2 emission reduction for product supply chain and CO2 end-of-pipe management has been successfully developed. This new methodology is expected to enable planners, policy makers or designers to plan and manage their CO2 emissions reduction effectively as well as systematically planning for resource conservation.